Venous variations in the region of the third ventricle: the role of MR venography - (:unkn) unknown (SPRINGER-VERLAG, 2003)
In this study, we examined the anatomical variations of the subependymal veins in the region of the foramen of Monro and the third ventricle by MR time of flight (TOF) venography. Fifty healthy subjects, ten patients with third-ventricle tumors, and four patients with lateral-ventricle tumors were included in the study. The courses of the anterior septal vein (ASV), thalamostriate vein (TSV), and internal cerebral vein (ICV) were studied. The proximity of the venous angle, the false venous angle, and the ASV-ICV junction to the posterior margin of the foramen of Monro was measured. In 69 (53.9%) sides, the ASV-ICV junction was located at the venous angle and at the posterior margin of the foramen of Monro. In 59 (46.1%) sides, the ASV-ICV junction was located beyond the foramen of Monro. Our study shows the high incidence of posteriorly located ASV-ICV junctions, which can be crucial in the planning of a better surgical approach. We strongly recommend that MR venography, which is a short radiological examination, be used before one operates on third-ventricle and lateral-ventricle tumors.
Keywords: foramen of Monro; MR venography; subependymal veins; transcallosal approach; ventricle; tumor; DURAL SINUS THROMBOSIS; TRANSCALLOSAL REMOVAL; ANGLE; LESIONS; ANATOMY; SYSTEM; BRAIN; VEINS